“A close read of my classroom”: Teacher research and identity work - Joy Kammerer Myers (Networks: An Online Journal for Teacher Research, 2016)
It is not uncommon for classroom teacher researchers to face multiple obstacles, but for the fifth grade teacher in this study, Donna, her administrators did not support her research efforts because they thought it would take away from preparing students for end of grade tests. The purpose of this study was to explore the ways conducting teacher research shaped Donna’s teacher identities and to examine how the context of her school impacted any identity shifts. Data sources included: interviews, observations, and teacher-created artifacts such as annotations of journal articles; her research proposal, paper, and presentation; reflections; and classroom observations. Findings indicate that instead of being discouraged, Donna persisted because she believed that the research she was doing in her classroom helped her see her students and teaching in new ways. In particular, she was able to participate in meaningful, self-selected professional development while at the same time improving her classroom instruction.